TECHNOLOGY AND THEOLOGY: AN UNEASY RELATIONSHIP - Canceran, Delfo Cortina (Asian Horizons, 2014)
This article is a critique of theology in general. In this cyberspace age, we can no longer gloss over the ubiquity of the internet in our lives. The internet has transformed our lives across all generations and occupations in varying degrees. Theology and theologians are not exempt from this great ongoing transformation. We need to face it in order to be relevant to people. First, the identity of theologians has been affected by the internet and theologians have to negotiate their identity. They have to take advantage of this ubiquitous internet in theologizing to the public. Second, theology has to be transformed from being anthropocentric and elitist to being cyberspacial and democratic in public conversation. We need to allow freedom and right of the people to express their thoughts and ideas responsibly and to provide spaces for cries and voices of the people in their search for democracy and change.